6+2x-5=6-3(2x-1)

Simple and best practice solution for 6+2x-5=6-3(2x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+2x-5=6-3(2x-1) equation:


Simplifying
6 + 2x + -5 = 6 + -3(2x + -1)

Reorder the terms:
6 + -5 + 2x = 6 + -3(2x + -1)

Combine like terms: 6 + -5 = 1
1 + 2x = 6 + -3(2x + -1)

Reorder the terms:
1 + 2x = 6 + -3(-1 + 2x)
1 + 2x = 6 + (-1 * -3 + 2x * -3)
1 + 2x = 6 + (3 + -6x)

Combine like terms: 6 + 3 = 9
1 + 2x = 9 + -6x

Solving
1 + 2x = 9 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
1 + 2x + 6x = 9 + -6x + 6x

Combine like terms: 2x + 6x = 8x
1 + 8x = 9 + -6x + 6x

Combine like terms: -6x + 6x = 0
1 + 8x = 9 + 0
1 + 8x = 9

Add '-1' to each side of the equation.
1 + -1 + 8x = 9 + -1

Combine like terms: 1 + -1 = 0
0 + 8x = 9 + -1
8x = 9 + -1

Combine like terms: 9 + -1 = 8
8x = 8

Divide each side by '8'.
x = 1

Simplifying
x = 1

See similar equations:

| 10h-8h+h-3h+h=7 | | 5+3(x+4)=-(2x-1)-9 | | log[4](13*7)= | | 5r^2-10r-15=0 | | 2x^3+13x=8x^2 | | -17-55p=5(2+4p)+2p | | 20-2=38 | | -3(x-4)+2xy=xy-5x+xy-6 | | 2w^2-22w+48=0 | | 5(2)-2=38 | | (3g+2)(9g+5)=0 | | 5(10)-2=38 | | 300+12=960 | | 6-(x+9)=3-4x | | 10x-7y=-42 | | (d-6)(d-2)=0 | | 3(8)+7=25 | | 8(x+1)+3=7x+18 | | 3x-5(x+2)=12x+4 | | (v-7)(v-6)=0 | | 0.27t=129 | | 3+x=43 | | 96c^2+336c+294=0 | | 2(3)-5=17 | | v^2=-14+9v | | 5y-3=10y+4 | | 4k(3k+4)=0 | | 96c+336+284=0 | | =9(-6-x)-8x | | x^4+x^2-720=0 | | 15(t-6)+3t=6(3t+3)-12 | | 45x-5y=6.6 |

Equations solver categories